Relevance of α-defensins (HNP1-3) and defensin β-1 in diabetes - Németh, Balázs Csaba (Baishideng Publishing Group Inc, 2014)
AIM: To investigate the genetic background of human defensin expression in type 1 and 2 diabetes. METHODS: Associations between DEFA1/DEFA3 gene copy number polymorphism and diabetes as well as between the promoter polymorphisms of DEFB1 and diabetes were studied. The copy number variation of the DEFA1/DEFA3 genes was determined in 257 diabetic patients (117 patients with type 1 and 140 with type 2 diabetes). The control group consisted of 221 age- and gender-matched healthy blood donors. The cumulative copy numbers of the DEFA1/DEFA3 genes were detected by using quantitative PCR analysis. To evaluate the HNP 1-3 (human neutrophil peptide 1-3 or α-defensin) levels in the circulation, plasma HNP 1-3 concentrations were measured by ELISA. The expression of DEFA1/A3 in peripheral leukocytes of the diabetic patients was measured by quantitative RT PCR analysis. Three SNPs of the human DEFB1 (human defensin β-1) gene: DEFB1 G-20A (rs11362), DEFB1 C-44G (rs1800972) and DEFB1 G-52A (rs1799946) were genotyped by Custom TaqMan(®) Real Time PCR assay. RESULTS: Significant differences were observed in HNP1-3 levels between the healthy subjects and both groups of diabetic patients. The mean ± SE was 28.78 ± 4.2 ng/mL in type 1 diabetes, and 29.82 ± 5.36 ng/mL in type 2 diabetes, vs 11.94 ± 2.96 ng/mL in controls; P < 0.01 respectively. There was no significant difference between patients with type 1 and type 2 diabetes in the high plasma concentrations of HNP1-3. The highest concentrations of α-defensin were found in diabetic patients with nephropathy (49.4 ± 4.8 ng/mL), neuropathy (38.7 ± 4.8 ng/mL) or cardiovascular complications (45.6 ± 1.45 ng/L). There was no significant difference in the cumulative copy numbers of DEFA1/DEFA3 genes between controls and patients, or between patients with the two types of diabetes. Comparisons of HNP 1-3 plasma level and DEFA1/A3 copy number of the same patient did not reveal significant relationship between defensin-α levels and the gene copy numbers (r(2) = 0.01). Similarly, no positive correlation was observed between the copy numbers and the mRNA expression levels of DEFA1/A3. Regarding the C-44G polymorphism of DEFB1, the GG “protective” genotype was much less frequent (1%-2%) among both groups of patients than among controls (9%). CONCLUSION: Elevated HNP1-3 levels in diabetes are independent of DEFA1/DEFA3 copy numbers, but GG genotype of C-44G SNP in DEFB1 gene may result in decreased defensin β-1 production.